2019
DOI: 10.1093/mnras/stz2272
|View full text |Cite
|
Sign up to set email alerts
|

Helium settling in F stars: constraining turbulent mixing using observed helium glitch signature

Abstract: Recent developments in asteroseismology -thanks to space-based missions such as CoRoT and Kepler -provide handles on those properties of stars that were either completely inaccessible in the past or only poorly measured. Among several such properties is the surface helium abundance of F and G stars. We used the oscillatory signature introduced by the ionization of helium in the observed oscillation frequencies to constrain the amount of helium settling in F stars. For this purpose, we identified three promisin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 65 publications
(91 reference statements)
1
13
0
Order By: Relevance
“…Whereas they make no attempt to quantitatively constrain the mixing processes, they emphasise the need to include such models in studies of stellar populations and chemical evolution. Verma & Silva Aguirre (2019) showed that the analysis of acoustic glitches in asteroseismic data can be used to constrain turbulent mixing. Their results for three Kepler targets yielded log T 0 in the range from 5.9 to 6.0, when comparing the effect on surface abundances, which is also slightly higher compared to our results.…”
Section: A164 Page 12 Of 15mentioning
confidence: 99%
“…Whereas they make no attempt to quantitatively constrain the mixing processes, they emphasise the need to include such models in studies of stellar populations and chemical evolution. Verma & Silva Aguirre (2019) showed that the analysis of acoustic glitches in asteroseismic data can be used to constrain turbulent mixing. Their results for three Kepler targets yielded log T 0 in the range from 5.9 to 6.0, when comparing the effect on surface abundances, which is also slightly higher compared to our results.…”
Section: A164 Page 12 Of 15mentioning
confidence: 99%
“…Théado et al 2005), through their impact on the equilibrium structure, in particular the suppression of near-surface convection discussed in Section 2.2. Moreover, a realistic transport of chemical elements (including atomic diffusion) currently requires the addition of a parametric turbulent diffusion coefficient in order to prevent the complete depletion of helium and metals from the surface, and reproduce surface abundances of F and A-type stars (Richer et al 2000;Richard et al 2001;Michaud et al 2011;Verma & Silva Aguirre 2019;Semenova et al 2020). Magnetic fields may also impact these competing mechanisms that are thought to be related either to mass loss or turbulence in Am stars (e.g.…”
Section: Stellar Modelsmentioning
confidence: 99%
“…When a parametrised turbulent diffusion coefficient is included in the model, we use the calibration proposed by Michaud et al (2011) to explain the surface abundances of Sirius A, which uses a reference mass M 0 = 2 × 10 −6 M (hereafter D turb,Am ). In order to test a more efficient transport (as suggested by our test of Section 5.3), we also use the parametrisation calibrated on three Kepler Legacy Ftype stars (Verma & Silva Aguirre 2019), with a reference mass of M 0 = 5 × 10 −4 M (hereafter D turb,F−Kepler ). Models are computed with the same input parameters as the models of the middle panel of Fig.…”
Section: Impact Of Chemical Element Transport Processesmentioning
confidence: 99%
“…Regions in stellar interiors where the sound speed undergoes an abrupt variation have been studied for several years in solar-type stars (e.g. Mazumdar et al 2014;García & Ballot 2019;Verma & Silva Aguirre 2019). The abrupt variation of the sound speed produces a quasi-periodic oscillatory component in the frequencies of stellar oscillations (e.g.…”
Section: Seismology Of Low-mass Stars: a Study For The Outer Convecti...mentioning
confidence: 99%